The use of historical approach in teaching communication arts to fast learners - Cabuniag, Antonia Hagunos (1974)
The purpose of the study was to apply the historical approach in the study of different literary types taken in high school, specifically for the third year high school fast learners. The study also aimed to show that the historical approach can be applied advantageously in teaching communication arts to fast learners. All teaching materials were taken from local sources with the aim of making the lessons meaningful to the actual life situations of the learners. The researcher found out that the historical approach puts high emphasis on scientific inquiry with which the five skills in historical research, such as, formulation of problems, making of hypothesis, collection of data, analysis, and generalization, serve as the basic points to be observed.